Direct Contraction Force Measurements of Engineered Cardiac Tissue Constructs With Inotropic Drug Exposure - Koivisto, Maria; Mosallaei, Milad; Toimela, Tarja; Tuukkanen, Sampo; Heinonen, Tuula (Frontiers in Pharmacology, 2022)
Contractility is one of the most crucial functions of the heart because it is directly related to the maintenance of blood perfusion throughout the body. Both increase and decrease in contractility may cause fatal consequences. Therefore, drug discovery would benefit greatly from reliable testing of candidate molecules effects on contractility capacity. In this study, we further developed our a dual-axis piezoelectric force sensor together with our human cell -based vascularized cardiac tissue constructs for cardiac contraction force measurements. The capability to detect drug-induced inotropic effects was tested with a set of known positive and negative inotropic compounds of isoprenaline, milrinone, omecamtiv mecarbil, propranolol or verapamil in different concentrations. Both positive and negative inotropic effects were measurable showing that our cardiac contraction force measurement system including a piezoelectric cantilever sensor and a human cell -based cardiac tissue constructs has potential to be used for testing of inotropic drug effects.